1956
DOI: 10.1042/bj0630044
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme systems in marine algae. The carbohydrase activities of unfractionated extracts of Cladophora rupestris, Laminaria digitata, Rhodymenia palmata and Ulva lactuca

Abstract: Present knowledge of the metabolism-of terrestrial plants and freshwater algae is considerable (cf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1958
1958
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…However, it does not differ between the control and each enzymatic treatment and may not influence the specific enzymatic action. Finally, the calculation of degradation percentage from the comparison between control and enzymatic digestion conditions may avoid having to account for non-specific hydrolysis by mechanical breaking and/or intrinsic proteolytic enzymes during the 6 h of agitation, as shown in some studies (Duncan et al 1956;Pérez-Lloréns et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, it does not differ between the control and each enzymatic treatment and may not influence the specific enzymatic action. Finally, the calculation of degradation percentage from the comparison between control and enzymatic digestion conditions may avoid having to account for non-specific hydrolysis by mechanical breaking and/or intrinsic proteolytic enzymes during the 6 h of agitation, as shown in some studies (Duncan et al 1956;Pérez-Lloréns et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes catalyzing analogous transfer reactions have been reported in extracts of Bacillius inacerans (25), blood plasma (22), germinated green gram (24), and minced algae (6). Similarily, a recently reported cabbage leaf enzyme (17) produced several oligosaccharides from concentrated maltose solutions.…”
mentioning
confidence: 67%
“…MEEUSE and SMITH (1962) have shown that granular starches from Ulva sp., and Codium fragile are broken down by oc-amylase preparations from various sources, including that from the mollusc Cryptochiton stelleri; this finding is relevant to the grazing of marine animals on seaweeds. Extracts of various marine algae including Cladophora rupestris and Ulva lactuca show the presence of both oc-amylase and oc-glucosidase activity, which could degrade starch by a hydrolytic pathway to the monosaccharide level (DUNCAN et al 1956). However, the overall level of activity of these extracts was so low that enzyme fractionaction studies could not be carried out.…”
Section: The Metabolism Of Marine Algal Starchesmentioning
confidence: 99%
“…In the first, xylan containing both (1 -> 3) and (1 -> 4)-linkages is present either as a separate xylan, or combined in a heteropolysaccharide, neither of which is skeletal material. In the second, the xylan is a linear component of the cell wall, and is either completely (1 -> 4)-linked, or completely xylosides (DUNCAN et al 1956, MANNERS andMITCHELL 1967). These activities could presumably form a hydrolytic pathway for the catabolism of algal xylans.…”
Section: Xylansmentioning
confidence: 99%